Application of The Contextual Teaching and Learning Strategy to Increase Studentsâ Successful in Mathematics Learning on Grade VIII at SMPN 6 Rambah - Nuraini, Nuraini (Proceedings of the 1st UR International Conference on Educational Sciences, 2017)
The success of the learning is depended on learning prosses by the teacher and the students. Based on the researcher experience as a teacher on grade VIII at SMPN 6 Rambah stated that many students did not get good score be based on KKM caused in learning proses used convensional method. According to National Education Department about Minimal Completeness Criteria (KKM):2008 stated that studentsâ total that achieved was 75 % from all the students in its class. The method of this research was Class Action Research by applied Contextual Teaching and Learning Strategy (CTL) and seven components of CTL such contructivism, inquiry, questioning, learning community, modeling, reflection, authentic assesment. The steps of the Contextual Teaching and Learning Strategy were : (1) motivating; 2. Understanding, 3. Applying and 4 scoring (Hartono, 2007). This research consist of 4 steps, they were : planning, implementation, observation and reflection. Those steps were did in 2 cycles and the object of the research were grade VIII at SMPN 6 Rambah. The result of this research showed that Contextual Teaching and Learning Strategy (CTL) can improved Studentsâ Successful in Mathematics Learning in grade VIII at SMPN 6 Rambah by given some lessons such surface area and volume of the cube flank, crossbar, prism and pyramid. Every learning had an increasing. from 28 students were 46,42%, whereas good were 75%. First cycle, students learning result were 67,85% and then second cycle were 85,71%.